MG-102 Coffin-siris syndrome caused by a missense mutation in arid1a. (4th December 2015) - Guerin, Andrea; Ahmed, Sohnee; Deardorff, Matthew; Carter, Melissa
Abstract : Coffin-Siris syndrome (CSS; OMIM # 135900) is caused by mutations in genes encoding components of the BRMassociated factor (BAF) complex, also known as the mammalian SWItch/sucrose nonfermentable (mSWI/SNF)-like complex. Clinical features are variable and may include hypoplasia of the distal phalanx of the fifth digit, developmental delay, dysmorphic or coarse facial features, growth restriction, and malformations of the brain, heart, and other organs. No widely accepted diagnostic criteria yet exist. Mutations in the ARID1A gene account for approximately 13% of CSS cases with eight patients reported to date. 1 Here we describe a 20-month-old boy with clinical features consistent with CSS, including feeding difficulties, hypotonia, speech delay, CNS anomalies, hypoplastic 5th digits, thick lower lip vermillion, and hypertrichosis. Our patient was found to have a de novo missense mutation (p. Leu1713Pro) in a highly conserved amino acid residue located in one of the leucine-rich motifs of ARID1A . All reported mutations of ARID1A associated with CSS thus far have been truncating, and are believed to be mosaic in lymphocytes. ARID1A heterozygous knock out mice are embryonic lethal, suggesting a vital role in embryonic development. Notably, while mutations in ARID1A noted in cancer are typically nonsense or frameshift, missense mutations in this same leucine-rich motif have been reported. These findings suggest several possibilities including: 1. This mutation resides in a critical position key to the function of ARID1A in human development; 2. This effect may be mild or specific enough to be tolerated and not cause lethality; or 3. This mutation causes moderate instability of the protein leading to a milder clinical presentation. Studies are underway to determine the functional consequences of this missense mutation on ARID1A mRNA and protein production. Reference: Kosho T, Okamoto N, Coffin-Siris Syndrome InternationalCollaborators. Genotype-phenotype correlation of Coffin-Siris syndrome causedby mutations in SMARCB1, SMARCA4, SMARCE1, and ARID1A. Am J Med Genet C Semin Med Genet . 2014;166C (3):262–75